Does Fertility Status Influence Impulsivity and Risk Taking in Human Females? Adaptive Influences on Intertemporal Choice and Risky Decision Making. (1st July 2013) - Kaighobadi, Farnaz; Stevens, Jeffrey R.
Informed by the research on adaptive decision making in other animal species, this study investigated human females' intertemporal and risky choices across the ovulatory cycle. We tested the hypothesis that at peak fertility, women who are exposed to environments that signal availability of higher quality mates (by viewing images of attractive males), become more impulsive and risk-seeking in economic decision tasks. To test this, we collected intertemporal and risky choice measures before and after exposure to images of either attractive males or neutral landscapes both at peak and low fertility conditions. The results showed an interaction between women's fertility status and image type, such that women at peak fertility viewing images of attractive men chose the smaller, sooner monetary reward option less than women at peak fertility viewing neutral images. Neither fertility status nor image type influenced risky choice. Thus, though exposure to images of men altered intertemporal choices at peak fertility, this occurred in the opposite direction than predicted—i.e., women at peak fertility became less impulsive. Nevertheless, the results of the current study provide evidence for shifts in preferences over the ovulatory cycle and opens future research on economic decision making.